Therapeutic advancement of benzothiazole derivatives in the last decennial period. Issue 1 (29th November 2018) - Tariq, Sana; Kamboj, Payal; Amir, Mohammad
Abstract: Benzothiazole, a fused heterocyclic moiety, has attracted synthetic and medicinal chemists for good reasons. It is a valuable scaffold that possesses diverse biological activities, such as anticancer, anti‐inflammatory, antimicrobial, antiviral, antimalarial, and anticonvulsant effects. This review mainly focusses on the recent research work on the different biological activities of benzothiazole‐based compounds. Abstract : This review mainly focuses on the research work on different pharmacological activities of benzothiazole‐based compounds carried out in the last decennial period. A list of patents is also included.